2019
DOI: 10.24293/ijcpml.v26i1.1394
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacteria Causes Ventilator Associated Pneumonia with Bronchoalveolar Lavage Culture and Endotracheal Aspirate Culture

Abstract: Ventilator associated pneumonia (VAP) is the most common hospital infection in ICU. Proper and prompt diagnosis and treatment with adequate antibiotics can reduce the high mortality rate, and prevent complications and antibiotic resistance. Invasive methods, such as bronchoalveolar lavage can make a more accurate diagnosis and help with the choice of antibiotics, but require lung experts. While non-invasive methods, such as endotracheal aspirate can be done faster with less complications. The aim of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In 2019, Asty et al found that the sensitivity and specificity of ETA cultures compared to BAL were very good at 78.9% and 75%, respectively. Therefore, they suggested that ETA be used as an alternative to diagnose suspected VAP cases (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Asty et al found that the sensitivity and specificity of ETA cultures compared to BAL were very good at 78.9% and 75%, respectively. Therefore, they suggested that ETA be used as an alternative to diagnose suspected VAP cases (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies state that the result of invasive techniques such as bronchoalveolar lavage (BAL) is superior and associated with better prognosis in comparison to non-invasive procedures such as endotracheal aspirate (ETA). Meanwhile, others believe that ETA can be used as an alternative to BAL as there is no significant difference between the results of the two sampling techniques (13) .…”
Section: Introductionmentioning
confidence: 99%